ANALYSIS OF ISLAMIC RELIGION EDUCATION LEARNING ON INDEPENDENT CURRICULUM BASED ON SCHOOL ORIGIN - Sabarudin, Mohammad; Al Ayyubi, Ibnu Imam; Fitriyah, Dzul; Diba, Davina Indah Farrasyah; Setiawan, Siti Sawwa Rahmawati; Sholeh, Muh Ibnu; Ho, Pham Vu Phi (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the application of Islamic Religion Education learning to student learning outcomes in an independent curriculum that gives students flexibility and independence in learning based on school origin. This research was conducted at SMPN 1 Wanayasa, SMPN 1 Rawamerta, SMPN 1 Cisarua, SMPN 2 Parongpong, and SMPN 2 Ciampel with a quantitative research approach. This research method uses survey method and Analysis of Variance test analysis with a sample of 31 students at SMPN 1 Wanayasa, 42 students at SMPN 1 Rawamerta, 33 students at SMPN 1 Cisarua, 35 students at SMPN 2 Parongpong, and 38 students at SMPN 2 Ciampel with a total of 179 students in inferential statistical analysis. In this study, it was found that there were differences that occurred at SMPN 1 Wanayasa, SMPN 1 Rawamerta, SMPN 1 Cisarua, SMPN 2 Parongpong, and SMPN 2 Ciampel. Then the differences that occur between the five schools show that differences in student learning outcomes occur at SMPN 1 Wanayasa with SMPN 1 Rawamerta, SMPN 1 Cisarua, SMPN 2 Parongpong, and SMPN 2 Ciampel, then SMPN 1 Rawamerta with SMPN 1 Ciarua and SMPN 2 Ciampel, and SMPN 1 Cisarua with SMPN 2 Parongpong. Whereas in SMPN 1 Rawamerta with SMPN 2 Parongpong, SMPN 1 Cisarua with SMPN 2 Ciampel, and SMPN 2 Parongpong with SMPN 2 Ciampel there is no difference. Thus, further research is expected to analyze the differences and interactions that occur based on learning outcomes, school origin, and student gender to be able to produce more elementary conclusions.